2001
DOI: 10.1016/s0002-9440(10)61770-1
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of Fetal RNA-Binding Protein p62 in Liver Cancer and Liver Cirrhosis

Abstract: p62 is a RNA-binding protein that was isolated by immunoscreening a cDNA expression library with autoantibodies from patients with hepatocellular carcinoma (HCC). This autoantigen binds to mRNA encoding insulin-like growth factor II, which has been found to be overexpressed in HCC and is tumorigenic in transgenic animals. Immunohistochemical analysis of HCC liver showed that 33% (9 of 27) exhibited readily detectable staining of p62 protein in the cytoplasm of all malignant cells in cancer nodules, whereas it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 39 publications
5
74
1
2
Order By: Relevance
“…Online promoter prediction programs used included PromoterInspector and Gene2Promoter from GenomatixSuite, 5 grailEXP (Grail Experimental Gene Discovery Suite), 6 and PROSCAN. 7 Combination of the obtained predictions resulted in the identification of two putative gene-regulatory regions for the mouse Imp2 gene (Fig. 1B, light gray bars).…”
Section: Regulatory Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Online promoter prediction programs used included PromoterInspector and Gene2Promoter from GenomatixSuite, 5 grailEXP (Grail Experimental Gene Discovery Suite), 6 and PROSCAN. 7 Combination of the obtained predictions resulted in the identification of two putative gene-regulatory regions for the mouse Imp2 gene (Fig. 1B, light gray bars).…”
Section: Regulatory Regionsmentioning
confidence: 99%
“…5,6), classifying them as oncofetal proteins. Concerning IMP2, Lu et al (7) detected overexpression of a splice variant of IMP2 (p62) in liver cancer (hepatocellular carcinoma and cholangiocarcinoma), and Zhang et al (8) found autoantibodies in sera of more than 10% of patients with esophageal, hepatocellular, lung, lymphoma, pharyngeal, or uterine cancer. Testing for the presence of such autoantibodies against a panel of autoantigens, including IMP proteins, has been proposed as a valuable tool for cancer detection and diagnosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…proteolytic cleavage, phosphorylation, and oxidation) associated with aberrant cell death may enhance their immunogenicity under a proinflammatory environment (39 -43). Other possibilities are that specific autoantigens are fetal proteins aberrantly expressed in tumor cells (44) or expressed in abnormally high amounts in tissues affected by autoimmune disease, inflammatory disease, or cancer, contributing to loss of immune tolerance to these antigens (45).…”
Section: Cancer-associated Autoantibodies As Reporters Of Tumorigenesismentioning
confidence: 99%
“…The mechanism underlying the production of such autoantibodies are not completely understood but the available data show that many of the target antigens are cellular proteins whose aberrant regulation could lead to tumorigenesis, such as p53 [8], HER-2/neu and ras [9,10], or are proteins whose dysregulation could have tumorigenic potential including mRNA binding proteins such as p62 [5] and cell-cycle control proteins such as cyclin B1 [11,12]. In the case of p62 which is primarily expressed in fetal tissues and is absent in adult tissues, immunogenicity appears to be related to abnormal expression of p62 in tumor cells [13]. In previous studies, we have observed changes in autoantibody profiles predating or coincident with clinical detection of liver cancer in chronic liver disease patients [14,15].…”
Section: Introductionmentioning
confidence: 99%